Proceso de bilingüismo en la literatura de la región de Huancavelica - Matamoros Dorote, Augusto (2023)
The study tries to answer the question: what are the characteristics of literature in the Huancavelica region as a bilingual society? The results show the bilingual character without diglossia, the topics they address are topics related to the activities of the Andean world of a magical religious, agrarian, livestock, mining and social violence nature. The literature of the Huancavelica region, due to its bilingual character without diglossia, is in the process of overcoming the traditional conception of diglossic bilingualism, in the thematic aspect, the literature, due to its dynamic character, addresses various themes, traditional and modern, regional but also universal issues